Pengaruh Formulasi Jamur Tiram Putih (Pleurotus oestreatus) dan Tapioka Terhadap Sifat Fisik, Organoleptik, dan Kimia Kerupuk - Astuti, Sussi; A.S., Suharyono; Fitra, Nopena (Jurnal Penelitian Pertanian Terapan, 2016)
White oyster (Pleurotus oestreatus) mushroom has high nutrition content. The white oystermushroom processing to be cracker product is one of product diversification efforts frommushroom. This research was conducted to find out the best formulation of tapioca andoyster mushroom to produce the best characteristics of oyster mushroom crackers. Thesecharacteristics include expansion volume, sensory, and chemist. This research was designedin a Completely Randomized Block Design with 3 replication. The treatments had 7formulation levels of tapioca and oyster mushroom flour, that were N1 (0% : 100%), N2(10% : 90%), N3 (20% : 80%), N4 (30% : 70%), N5 (40% : 60%), N6 (50% : 50%), and N7(60% : 40%), respectively. Data were analiyzed with analysis of varians to find out thetreatment effects, then the data were further analyzed with Honestly Significant Difference(HSD) test on level of 5% to find the best formulation. The results showed that formulationN2 (10% white oyster mushroom and 90% tapioca) was the best formulation with expansionvolume of 452,28%, crunchy texture, rather-typical of oyster mushroom taste, rather-typicalof oyster mushroom aroma, water content of 7,20% (%db), ash content of 1,03% (%db), fatcontent of 0,46% (%db), protein content of 1,66% (%db), and fibre content of 0,24% (%db).However, the protein content didn?t include the qualification of cracker standard quality(SNI 01-2713-1999).Keywords : white oyster mushroom, tapioca, cracker